'Naked abroad': The continuing imperialism of free trade. (October 2014) - Grocott, Chris; Grady, Jo
This article draws on Gallagher and Robinson (1953) and combines their concepts with insights offered by, amongst others, Callinicos, Eagleton and Harvey, in order to demonstrate continuities between British and US imperialism. They include the willingness of states to engage in imperial action (despite public statements of anti-imperial sentiment); the use of formal and informal control to secure the frontiers of a state's expanding economy; and the operation of imperialism through collaboration. In order to avoid the problems of earlier Marxist-Leninist interpretations of British imperialism, and in order to extend the analysis, the concepts of ideology, elites and neoliberalism are applied.